To Flex or Rest: Does Adding No-Load Isometric Actions to the Inter-Set Rest Period in Resistance Training Enhance Muscular Adaptations? A Randomized-Controlled Trial - Schoenfeld, Brad J.; Grgic, Jozo; Contreras, Bret; Delcastillo, Kenneth; Alto, Andrew; Haun, Cody; De Souza, Eduardo O.; Vigotsky, Andrew D. (Frontiers in Physiology, 2020)
We aimed to investigate the effects of resistance training (RT) combined with no-load isometric actions (iso-holds) during the inter-set recovery period versus RT that involves passive inter-set rest on muscular strength, muscular hypertrophy, and muscular endurance in resistance-trained men. Twenty-seven resistance-trained male volunteers were randomly assigned to either a traditional group (TRAD) that performed a hypertrophy-oriented RT routine with the rest intervals spent passively (n=13) or to a group that supplemented traditional RT with iso-holds (ISO) for the working muscle group between each set (n=14). Training for both routines consisted of 3 weekly sessions performed for 8 weeks. Three sets of 8-12 repetitions were performed per exercise. A 2-minute rest interval was afforded between sets; the ISO group performed iso-holds for the first 30 seconds of each rest interval and then recovered for the final 90 seconds. Maximal strength was assessed using the one repetition maximum (1RM) tests in the leg press and bench press. Upper-body muscle endurance was assessed by performing the bench press to failure at 50% of 1RM. Muscle thickness of the elbow flexors, elbow extensors, mid-thigh, and lateral thigh was assessed using B-mode ultrasound. Results indicated a favorable effect of ISO on muscle thickness in the mid-thigh. Alternatively, there was a possible detrimental effect for ISO on leg press strength. No other notable differences were seen between conditions. In conclusion, the use of inter-set iso-holds may be a time-efficient strategy to enhance development of the quadriceps femoris; conversely, it may be detrimental to maximizing lower body strength.